2006
DOI: 10.1097/01.ajp.0000210909.49923.df
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interdisciplinary Treatment for Chronic Nonmalignant Pain Patients in Japan

Abstract: Our results suggest that an interdisciplinary treatment based upon the biopsychosocial model of pain was associated with significant improvement in multiple outcomes in this sample of Japanese patients with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…19 Although opioids are generally available and concerns about undertreatment of pain exist, alternative approaches and tools for the treatment of chronic pain are emphasized, with substantially lower quantities of opioids prescribed. [46][47][48] Overall, medical system culture -including less commercialization in health care and less influence from the pharmaceutical industry and advertising -has been found to play a role in differentiating levels of opioid use in different contexts: some practices rely less on pharmacotherapy to deal with pain. 49,50 Consequently, opioid-related harms as observed in North America are considered uncommon elsewhere (e.g., in Europe).…”
Section: Evidence From Abroadmentioning
confidence: 99%
“…19 Although opioids are generally available and concerns about undertreatment of pain exist, alternative approaches and tools for the treatment of chronic pain are emphasized, with substantially lower quantities of opioids prescribed. [46][47][48] Overall, medical system culture -including less commercialization in health care and less influence from the pharmaceutical industry and advertising -has been found to play a role in differentiating levels of opioid use in different contexts: some practices rely less on pharmacotherapy to deal with pain. 49,50 Consequently, opioid-related harms as observed in North America are considered uncommon elsewhere (e.g., in Europe).…”
Section: Evidence From Abroadmentioning
confidence: 99%
“…The only other study that has included pain self-management in an Asian country was reported by Kitahara et al [18] from Japan. This study found that an interdisciplinary approach (that included some cognitive and behavioural methods) with individual chronic pain patients was helpful in improving levels of pain and activity as well as reducing use of inappropriate medication.…”
Section: Discussionmentioning
confidence: 99%
“…Why there have not been more such studies from Asia is unclear, but it may reflect the limited pain clinic and rehabilitation resources in this region [18, 27]. Our experience in Malaysia is that injured workers are expected to return to work despite persistent pain, especially if the ‘usual’ healing period for that particular injury has passed and the only reason cited for not returning to work is pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in Europe and North America, the multidisciplinary pain management approach, based on a biopsychosocial model and including CBT, has been widely recommended as a standard chronic pain management treatment approach [13][14]. This approach is less common in Southeast Asia [15][16].…”
Section: Psychological Treatments For Chronic Painmentioning
confidence: 99%